(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Today fast communication technologies are the need for modern communication and computer networks as well as the Internet. They are developed for transmission of huge amounts of information, for which Congestion Control Algorithms (CCAs) are most powerful. A congestion control method is one of the essential that keep any network energetic and decent for the users. Various algorithms suggested recently trying to provide an efficient control of congestion that occurs in the network. Active Queue Management (AQM) is one of such method which provides superior control in congestion control. This paper concentrates on active queue management established congestion control algorithms to discuss performance parameters designed for networks stable as well as optimal (minimum) queue length and issues about the merits and demerits of the congestion control algorithms and evaluate their features. Keywords: Congestion; Congestion Control; Communication Network; Active Queue Management; Throughput, Latency